A Comparison of the Research Approaches of Capital in the Twenty-First Century and Capital. Issue 3 (2nd July 2016) - Xiaoping, Wei
ABSTRACT: In Capital in the Twenty-First Century, Thomas Piketty uses global macroeconomic statistical data to show that, in the distribution of national wealth, the rate of return on capital is always greater than the rate of economic growth ( r > g ). He demonstrates a trend toward the concentration of wealth, which, to a certain extent, means a trend toward a hereditary system of the concentration of wealth, and away from wealth through hard work. In some respects, Piketty's argument verifies the basic view of Marx that surplus value is concentrated at the end of capital. However, unlike Marx's criticism of relations of production, the goal of Piketty's research is to improve the capitalist system. He advocates progressive wealth taxation and its global implementation to curb limitless increases in profit.